Cerebral Hemodynamic Changes After Revascularization in Patients With Hemorrhagic Moyamoya Disease - Kang, Kaijiang; Ma, Ning; Li, Jinxin; Shen, Yuan; Gu, Weibin; Ma, Guofeng; Zhang, Dong; Zhao, Xingquan (Frontiers in Neurology, 2020)
Objective- To explore the cerebral hemodynamic changes after revascularization in patients with hemorrhagic moyamoya disease (MMD). Materials and Methods- We retrospectively included 57 hemorrhagic MMD patients in a high-volume stroke center from January 2016 to December 2018. All subjects were evaluated with whole-brain CT perfusion (CTP) before and after surgical revascularization. Absolute and relative CTP values in the regions of cortical middle cerebral artery territory (CMT) and deep brain area (DBA) of hemorrhagic hemispheres were measured. Differences between pre- and post-operative CTP values were assessed comprehensively. The patients were categorized into subgroups based on revascularization subtypes and postoperative CTP intervals. Results- The relative cerebral blood volume (rCBV) in DBA and CMT significantly reduced in postoperative CTP (P<0.05). The median and interquartile range of the proportion of rCBV decrease (rCBVc%) were 7.2% (2.3%-13.2%). The rCBV reduction retained statistical signiﬁcant in patients who received subtypes of revascularization, and in patients with variable intervals of follow-up (P<0.05). There was no significant difference of rCBVc% between patients who received different revascularization and among patients with different postoperative CTP intervals (P>0.05). The relative mean transit time (rMTT) and relative time to peak (rTTP) also showed downward trends, but without retainable statistical signiﬁcance in stratified analysis. There was no significant change in relative cerebral blood flow (rCBF) (P˃0.05). Conclusion- In patients with hemorrhagic MMD, the CBV appeared to decrease and be relatively stable in the chronic phase after revascularization, with varying degrees of MTT and TTP shortening. However, there was no significant change in CBF.